IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN BACA TULIS AL-QUR’AN (BTQ): ANALISIS KESENJANGAN ANTARA NILAI DAN PERILAKU SISWA - Zulfa Uswatun Hasanah; Muh. Wasith Achadi; Rosyida Rakhmania Muha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of religious literacy and the emergence of a character crisis among students, reflecting a discrepancy between the values taught in schools and students’ actual behavior. The study aims to analyze the implementation of Qur’anic Reading and Writing (Baca Tulis Al-Qur’an/BTQ) learning in character formation, examine its impact on students’ behavioral changes, and identify the gap between values and practices within the school environment. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving teachers and students as research informants. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and technique triangulation. The findings reveal that BTQ learning not only enhances students’ ability to read the Qur’an but also serves as a medium for the internalization of character education through habituation, exemplary conduct, and motivational reinforcement. The implementation of BTQ learning contributes to the improvement of students’ religiosity, discipline, and social attitudes. However, these changes have not been evenly manifested among all students, indicating the persistence of a gap between the values conveyed in learning and students’ actual behavior. This discrepancy is influenced by internal factors, external factors, and the existing learning system. The study concludes that BTQ learning plays a strategic role in shaping students’ character; nevertheless, greater emphasis on evaluation aspects and instructional strategies is required to optimize the internalization of values.